Comparative safety of selective serotonin reuptake inhibitors among pediatric users with respect to adverse cardiac events1. (4th March 2013) - Czaja, Angela S.; Valuck, Robert J.; Anderson, Heather D.
ABSTRACT Purpose This study aims to perform a comparative safety study assessing the risk of ventricular arrhythmia, cardiac arrest, or sudden death among pediatric selective serotonin reuptake inhibitor (SSRI) users. Methods Using US claims data from 1997 to 2009, new pediatric (age < 18 years) users of SSRI monotherapy were identified. Adverse cardiac outcomes occurring within 12 months of SSRI initiation were identified using a previously validated International Classification of Disease, ninth edition algorithm. Cox proportional hazard analysis was used to estimate the risk for each SSRI, using fluoxetine as the referent group, adjusting for the propensity to receive an individual SSRI, demographics, and exposure covariates. Results Over the study period, 113 714 subjects met the inclusion criteria and contributed 40 639 person‐years of SSRI exposure time. Sertraline (33%) and fluoxetine (29%) were the most commonly prescribed SSRIs. Forty events occurred within 12 months of SSRI initiation. The crude incidence rate was highest for escitalopram (19.5/10 000 person‐years) and lowest for fluoxetine (4.2/10 000 person‐years). The median time to event ranged from 45 to 86 days. The adjusted risk of adverse event, relative to fluoxetine, was highest for citalopram Hazard Ratio (HR) = 3.53, 95% confidence interval [CI] = 1.09–11.46) and escitalopram (HR = 3.30, 95%CI = 1.08–10.14) and lowest for paroxetine (HR = 1.34, 95%CI = 0.30–5.99) and sertraline (HR = 2.14, 95%CI = 0.75–6.16). Conclusions The incidence of adverse cardiac events among pediatric SSRI users was low. However, the risk of an adverse outcome was higher for citalopram and escitalopram users as compared with fluoxetine users. Future studies should focus on confirming these findings and identifying modifying risk factors to optimize medication selection for this population. Copyright © 2013 John Wiley & Sons, Ltd.